Body lipid composition modulates acute cadmium toxicity in Daphnia magna adults and juveniles. (August 2018) - Ferain, Aline; De Saeyer, Nancy; Larondelle, Yvan; Rees, Jean-François; Debier, Cathy; De Schamphelaere, Karel A.C.
Abstract: Long chain polyunsaturated fatty acids (LC-PUFAs) such as eicosapentaenoic acid (EPA, 20:5n-3) affect zooplankton fitness and ability to cope with environmental stressors. However, the impact of LC-PUFAs on zooplankton sensitivity to chemical stressors is unknown. Here, we aimed to document the interaction between EPA and cadmium (Cd), as model chemical stressor, in Daphnia magna . A life-history experiment was performed in which daphnid neonates were raised into adulthood on three diets of different lipid composition: (i) algae mix; (ii) algae mix supplemented with control liposomes; (iii) algae mix supplemented with liposomes containing EPA. Juveniles (3rd, 4th and 5th brood) released by daphnids during this life-history experiment were sampled, challenged with Cd during 48 h and their immobility was assessed. At the end of this life-history experiment, another immobilisation test was performed with adults from each treatment. Daphnids absorbed, incorporated and transferred ingested EPA to their offspring. Liposome feeding increased adult tolerance to Cd. The presence of EPA in liposomes did not increase adult tolerance to Cd. Offspring's tolerance to Cd was influenced by the brood number and the maternal diet. It was positively correlated with the PUFA level in body neutral lipids, especially alpha-linolenic acid (ALA, 18:3n-3) and negatively correlated with the saturated fatty acid level in body neutral lipids, especially stearic acid (18:0). Overall, these results emphasize the importance of dietary lipids and maternal transfer of body lipids in D. magna sensitivity to Cd and highlight the need to take into account these parameters in ecotoxicological studies and risk assessment. Highlights: Dietary liposome supplementation protects adult daphnids against acute Cd challenge. Offspring tolerance to Cd is influenced by neutral lipid richness in ALA and 18:0. Daphnids absorb, incorporate and transfer ingested EPA to their offspring. EPA supplementation does not confer an additional protection against Cd. Maternal transfer of body lipids is influenced by the diet and the brood number.